2017
DOI: 10.1007/s11259-017-9701-1
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin influences bovine herpesvirus 1 replication through upregulation of SIRT3 and cytoskeletal reorganization

Abstract: Infection of kidney cells (MDBK) with Bovine Herpesvirus 1 (BoHV-1) is affected by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), which accelerates BoHV-1-induced apoptosis and increases virus replication. Herein, to elucidate the mechanism through TCDD modifies BoHV-1 infection, we analyzed the modulation of a members of Sirtuin proteins family in MDBK cells. We found that mitochondrial SIRT3 was upregulated during infection. This change was accompanied by cytoskeletal rearrangements and cell extensions. All the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…TCDD (Supelco, 48599) was initially diluted to give a 10, 000pg/ml stock solution by mixing with DMEM. This stock solution was then diluted to give a working solution of 1pg/ml in DMEM, which was added to cultures [4,[19][20][21][22][23][24][25]30].…”
Section: Cell Culturesmentioning
confidence: 99%
See 3 more Smart Citations
“…TCDD (Supelco, 48599) was initially diluted to give a 10, 000pg/ml stock solution by mixing with DMEM. This stock solution was then diluted to give a working solution of 1pg/ml in DMEM, which was added to cultures [4,[19][20][21][22][23][24][25]30].…”
Section: Cell Culturesmentioning
confidence: 99%
“…In human SH-SY5Y neuronal cell line, Morales-Hernandez et al [15] have related TCDD toxicity to a disruption of calcium homeostasis while others [16][17][18] have established that the Aryl Hydrocarbon Receptor (AhR), to which TCDD binds with a high affinity, is involved in mediating the diverse toxic responses of this dioxin. In Madin-Darby Bovine Kidney (MDBK), an epithelial cell line, through AhR [19,20], TCDD induced a significant cell proliferation [21], increased the incidence cell death with autophagy [19,20,22] and promoted the Bovine Herpesvirus-1 (BoHV-1) infection as well as BoHV-1-induced apoptosis [4,[19][20][21][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a nuclear replicating virus, BoHV-1 infection induces oxidative DNA damage in multiple cell cultures, such as bovine kidney cells (MDBK) and human A549 lung carcinoma epithelial cells, as demonstrated by the increased production of DSBs analyzed by comet assay [ 10 , 13 , 14 ]. Accumulating studies have indicated that damaged DNA can activate various cell death pathways [ 13 ], and BoHV-1infection induces diverse forms of cell death both in vivo and in vitro [ 14 , 15 , 16 , 17 , 18 , 19 ], which underscores the implication of virus-infection-induced DNA damage in the virus pathogenesis. In addition, as an oncolytic virus, BoHV-1 infection in human lung adenocarcinoma cells A549 results in cell lesions partially by inducing DNA damage [ 10 ], which underlies the importance of DNA damage in the virus oncolytic effects.…”
Section: Introductionmentioning
confidence: 99%